Syntax of Dutch. - Broekhuis, Hans, 1959-; Keizer, Evelien; Dikken, Marcel den, 1965-; Bennis, Hans.; Gorver, Norbert; Vos, Riet. (Amsterdam : Amsterdam University Press, 2012)
The Syntax of Dutch will be published in at least seven volumes in t he period 2012-2016 and aims at presenting a synthesis of the currently available syntactic knowledge of Dutch. It is primarily concerned with language description and not with linguistic theory, and provides supp ort to all researchers interested in matters relating to the syntax of Dutch, including advanced students of language and linguistics.
[Vol. 1] Nouns and noun phrases : volume 1 / HansBroekhuis, Ev elien Keizer ; with the cooperation of Hans Bennis ... [et al.] -- [ vol. 2] Nouns and noun phrases : volume 2 / Hans Broekhuis, Marce l den Dikken ; with the cooperation of Hans Bennis ... [et al.] -- [ vol.3] Adjectives and adjective phrases / Hans Broekhuis -- [v ol. 4] Adpositions and adpositional phrases / Hans Broekhuis ; wi th the cooperation of Hans Bennis ... [et al.] -- [vol. 5] Verbs and verb phrases : volume 1 / HansBroekhuis, Norbert Gorver, and Rie t Vos -- [vol. 6] Verbs and verb phrases : volume 2 / Hans Bro ekhuis and Norbert Corver.
Text in English with some Dutch.
Keywords: Dutch language -- Syntax; Dutch language -- Syntax